Dynamics of discrete entrainment of the circadian rhythm in the rat pineal N-acetyltransferase activity during transient cycles - Illnerová, H; Vanĕcek, J (Journal of biological rhythms, 1987)
To elucidate entrainment of a pacemaker controlling the N-acetyltransferase (NAT) rhythm in the rat pineal gland, we studied the phase response curves (PRCs) of this rhythm. We exposed 50- to 60-day-old male Wistar rats maintained in a light-dark cycle (LD 12:12) to a 1-min light pulse at different times before midnight or at various times throughout the whole night. We then released them into constant darkness and studied the morning NAT decline during the night when rats were pulsed before midnight, as well as the evening NAT rise and the morning decline after 4 days following the pulses. The PRC for the first NAT decline and the PRCs for the NAT rise and decline after 4 days were compared with published transient PRCs (Illnerová and Vanĕcek, 1982b), in order to obtain a complete picture of the dynamics of the NAT rhythm entrainment during the transient cycles. Phase delays in the NAT rise due to a pulse before midnight were complete (i.e., identical to those of day 4) on day 1. Phase delays in the NAT decline were almost complete on day 1, while incomplete phase delays were observed on day 0. Phase advances in the NAT rise and decline due to a pulse past midnight had different dynamics: Advances in the decline were complete on day 1, while advances in the rise were absent on day 1 and much smaller than in the decline on day 4. The results are discussed in terms of a two-component (E-M) pacemaker controlling the NAT rhythm. The NAT rise may reflect the phase of the E-component, while the decline reflects the M-component. Phase delays of the E-component are accomplished within one cycle, and so are phase advances of the M-component. However, although delays of E already result in delays of M one cycle after the pulse, it takes several transient cycles before advances of M begin to induce advances of E.
Keywords: Acetyltransferases; Light; Circadian Rhythm; Rats; Rats, Inbred Strains; Animals; cirkadiánní rytmus; krysa rodu Rattus; mužské pohlaví; Male; světlo; zvířata; Pineal Gland; acetyltransferasy; epifýza mozková; inbrední kmeny potkanů